Novel approaches for the detection of low-density Mediterranean fruit fly populations - Eleftheria-Maria D. Bali; Eleni Verykouki; Dimitrios Papachristos; Spyridon Antonatos; Panagiotis Milonas; Nikos T. Papadopoulos (Biological Invasions, 2026)
Biological invasions pose a growing threat to global agriculture, biodiversity, and ecosystems with invasive insect species like the Mediterranean fruit fly (medfly) among the most notorious for fruit production and trading. Effective early detection of low-density populations is essential for limiting establishment and spread, particularly under conditions that favor population growth. In this study we tried to evaluate the detectability of low-abundance medfly populations using a novel release–recapture approach in urban environments across two regions of Greece. Feral marked males and females were released at randomized points in areas where the medfly is well established and occurs in high population levels, and recapture rates were monitored using standard traps baited with sex- and food-based attractants. Despite releasing 6480 adults over multiple trials, recapture rates remained very low (0.74%), with most individuals recaptured within the first 15 days post-release and in traps located near release points. Statistical modeling revealed that detection likelihood was influenced by the number of flies released and the distance to traps, while temperature and time after release had no measurable effect. Recapture patterns varied between sites, highlighting the influence of landscape structure, host plant availability, and microclimatic factors. These results demonstrate that detecting incipient invasions is inherently challenging and often influenced by stochastic processes. Surveillance systems relying on sparse trap grids may fail to detect early-stage populations, allowing invasive species to establish undetected. Enhancing trap density and integrating ecological variables into monitoring strategies are critical for improving early detection and informing timely eradication efforts.